RETRACTED: Energy Transition, Sustainable Development Opportunities, and Carbon Emissions Mitigation: Is the Developed World Converging Toward SDGs-2030? - Lyu, Yixin; Ali, Syed Ahtsham; Yin, Weihua; Kouser, Robina (Frontiers in Environmental Science, 2022)
The success of sustainable development heavily depends on successful energy transition toward renewable or carbon-free energy sources. This study attempted to analyze the impact of sustainable development and environmental initiatives on sustainable energy transition in selected OECD economies. For this purpose, the study generated the dataset of environment air and GHG emission, environmental-related technologies, development (gross domestic product, trade openness, and gross domestic spending on R&D) and sustainable environment (air and GHG emission and environmental-related technologies), and energy sources (renewable energy consumption, nonrenewable energy consumption, and sum of total energy consumption) of selected economies of OECD between 2000 and 2020. This study utilized dynamic panel GMM for regression analysis, and FMOLS and DOLS were applied as the robustness models. Empirical results indicated that sustainable development and a sustainable environment contribute positively to the energy transition process in OECD economies. However, these factors also negatively contribute to non-renewable energy consumption in OECD. Thus, the study’s outcomes confirmed the sustainable energy transition in OECD. Therefore, this study suggested that the success of Sustainable Development Goals depends on successful energy transition.